Differences in quality of life based on coping strategies among caregivers of patients with schizophrenia - Azizah, Hidayatul; Afriyeni, Nelia; Puspasari, Dwi (University of Muhammadiyah Malang, 2026)
Schizophrenia is a chronic mental disorder that requires long-term caregiving support, often leading to substantial physical, psychological, social, and environmental burdens for caregivers. These burdens may affect caregivers’ overall quality of life. Coping strategies play an important role in managing caregiving demands and maintaining caregivers’ well-being. This study examined differences in caregivers’ quality of life based on three types of coping strategies: problem-focused, emotion-focused, and avoidance coping. A total of 130 caregivers of patients with schizophrenia receiving outpatient treatment at Prof. H. B. Saanin Psychiatric Hospital, Padang, participated in this study through purposive sampling. Data were analyzed using a one-way ANOVA. The Brief COPE and the Schizophrenia Caregiver Quality of Life Scale (S-CGQoL) were used as instruments. The results showed significant differences in quality of life across the coping strategy groups. Caregivers who used emotion-focused and problem-focused coping reported higher quality of life than those who used avoidance coping. These findings highlight the importance of promoting adaptive coping strategies to enhance caregivers’ quality of life.